The Location of Hotels and Their Exposure to Hurricanes in Cuba—Implication for Tourism Development in the Context of Climate Change - Ricardo Remond-Noa; Antonio Torres-Reyes; Felipe Matos-Pupo; Maite Echarri-Chávez; Antonio Bouta-Numbo; Lisbet Crespo-García; María Belén Gómez-Martín (Atmosphere)
This study focuses on the relationship between hotel sites (current and planned) and exposure to hurricanes in Cuba. The hypothesis focused on demonstrating that Cuban tourist areas have differing degrees of exposure to tropical cyclones according to the month. The results indicate that although the whole Cuban archipelago is exposed to hurricanes, the tourist regions in Cuba’s western provinces have a greater chance of being affected than those located in the center, east, and south. The tourism development that will take place by 2030 in Cuba includes significant hotel expansion in coastal areas that are highly exposed to hurricanes. Information on the risk of hurricanes in tourist regions provides information that could enable the creation of the organizational conditions needed to tackle these phenomena in the short to medium term and to refine spatial and tourism planning approaches in the long term.